Analysis of PSI Political Branding Behaviour in Twitter During Indonesia’ Legislative Election 2019 - Almira Kusumowardani Habsari (Universitas Muhammadiyah Yogyakarta, 2020)
This paper contributed to the body of knowledge on how new political party endorses themselves to attract people, especially millennials, to vote for them in the election by utilizing social medias. Therefore, this research aimed to cover the gap on the effectiveness of social media that was used by the new political party to endorse them to attract people to vote for them in 2019 election in Indonesia. Millennial generation grew in the era of advanced information technology that changed various aspects of life, especially the media. Millennials used the internet for almost everything including sending messages through social media. PSI's aim to attract millennials through social media was a strategy that was not only to give information about the leaders who would occupy new political positions, but also to educate politics to young people so that they could become leaders in the future. Hereby, the research methodology used qualitative interpretative content analysis approach: collecting all the tweets of PSI in campaign period and analyzed it using manual coding. Moreover, this study aimed to dig deeper understanding regarding the political branding on the case of the new political party.